TUNNEL COOLING FOR BYRD STATION, ANTARCTICA-1969 PROGRESS REVIEW. - Hoffman,Clark R. (1970)
Byrd Station is located in snow tunnels more than 20 feet below the surface of the antarctic continental ice cap. The accumulation of heat lost from the buildings and other facilities in the tunnels and summer surface air temperatures to plus 25F necessitates supplementary air cooling, to maintain the 0F design air temperature in the tunnels. To accomplish this, an experimental cooling system utilizing the heat sink represented by the surrounding snow field was constructed by military personnel and placed in operation in November 1969. Instrumentation installed by NCEL has conclusively demonstrated the feasibility of this system for cooling undersnow camps but shows the need for greater capacity if the 0F target is to be maintained. It is also found that improved air exhaust systems are required in the high-heat-source tunnels to prevent heat buildup in winter and permit independent operation of the plenum cooling system for conservation and restoration of its cooling capacity. (Author)